Surface modification of polydimethylsiloxane microchannel using air plasma for DNA capillary migration in polydimethylsiloxane–glass microfluidic devices. (1st June 2013) - Alsadat Rad, Maryam; Ibrahim, Kamarulazizi; Mohamed, Khairudin; Najimudin, Nazalan
Abstract : Polydimethylsiloxane (PDMS) microchannel surfaces were modified by air plasma to improve their applicability in microfluidics. The procedure included an increase in air plasma duration from 10 to 30 s. This resulted in an increase of wettability which was demonstrated by the decrease of water contact angles from 105° to 8°. The surface modification‐assisted PDMS microchannel easily bonded to a glass surface, and a PDMS/glass microfluidic device was fabricated with a simplified process. Slight pressure applied directly over the PDMS microchannel (approximate dimensions of 2.5 µm deep and 8.8 µm wide) formed nanoslits with dimensions of 830 nm in width and 170 nm in height on the PDMS/glass interface. Nanoslit formation was directly correlated to the metastable collapse of PDMS microchannels on the glass surface after the plasma treatment. The fabricated microfluidic devices were successfully employed for λ ‐DNA capillary migration without any external driving force.